Provider-Patient Communication of Personal Breast Cancer Risk (BCR): Providers' Beliefs [18M]. (May 2018) - Abittan, Baruch; Herman, Sarah; Herman, Jonathan
Abstract : INTRODUCTION: A woman's understanding of her own breast cancer risk (BCR) is an important precursor for care. Patients rely on their providers for accurate information and advice. The objective of this study was to understand the beliefs, practices and perceptions of providers in the primary female healthcare field, considering three areas: communication of mammography results, discussion of BCR with patients, and calculation of BCR for patients. METHODS: An online questionnaire consisting of 47 questions was administered between July and September of 2013 to Long Island-based women's health providers. Participants (N=174) consisted of 88 physicians (51%), 44 obstetric and gynecology resident physicians (25%), 29 midwives (17%), 7 nurse practitioners (4%), and 6 physician assistants (3%). RESULTS: 82% of providers agree that it is important to convey mammography results to their patients. 79% believe that it is important to discuss personal BCR with one's patient, but only 40% feel that it is important to calculate a patient's BCR. 14% of providers reported that they actually calculate personal BCR at every well visit, and an additional 19% report calculating personal BCR if prompted by the patient. 57% admit to not calculating personal BCR for their patients. 51% of providers report that they actually discuss personal BCR at every well visit, and another 30% discuss BCR if prompted by their patient. 9% of practitioners report that they do not discuss personal BCR. CONCLUSION: Understanding of providers' beliefs and practices is an initial step in improving communication of personal breast cancer risk between provider and patient.